Cultivation of White Button Mushroom (Agaricus bisporus) for Economic Empowerment of hill people : A study in Uttarakhand - Sharma, Arpita; S. K. Mishra (Mushroom Research, 2024)
The global market is witnessing an increasing trend for mushroom as a commodity due to a shift in consumers’ choices from animal protein to mushroom. Mushroom is a cash crop that is capable of harnessing a good amount of harvest from limited organic and financial resources. Mushroom cultivation offers a way for the socio-economic development of rural people due to its potential to create employment opportunities, poverty alleviation and eradication of malnutrition. Mushroom cultivation can also help to reduce susceptibility to poverty and strengthen livelihoods through the generation of fast yielding and nutritious source of food and reliable source of income. The government has initiated various projects and plans to disseminate awareness of mushroom cultivation in rural areas. The ICAR-Farmer FIRST Project is also one of the important initiative for strengthening rural communities. Training on "Mushroom cultivation and its value added products" was organised by Department of Agricultural Communication in joint collaboration with Mushroom Research and Training Centre, Govind Ballabh Pant University of Agriculture &Technology, Pantnagar in village Dogra, district Nanital, Uttarakhand. During the training, total 70 ready mushroom bags (with 10 kg compost each) were distributed to seventy farmers @10 bags/beneficiary. The results revealed that favourable change was noticed in the awareness and perception towards mushroom cultivation among the beneficiaries at the end of the intervention. Change in awareness level includes harvesting and processing methods (82.86%), preservation techniques, methods of compost making (91.43%), sorting/packaging (87.15%), handling techniques of sprayer and other equipment (81.43%), Type of mushroom (88.58%), Marketing Channel (77.15%), Government Schemes for mushroom growers (62.86%), Loans and Subsidies for mushroom growers (64.29%). Change in Perception level includes mushroom cultivation is a profitable venture, mushroom can be sold in local market (91.43%), mushroom has high nutritive value, mushroom’s value added products is available in market (81.43%).